Simulation of sympathetic cooling of helium-like 9Be2+ - Kai Zhu; Hong-fang Song (AIP Advances)
Helium and helium-like atomic systems are of significant interest in the study of few-body systems due to their simple structures. Nevertheless, current spectroscopic assessments of He-like ions, such as Li+ and Be2+, encounter constraints in precision owing to the formidable Doppler effect inherent in ion beam experiments. Addressing this challenge, we propose a methodology of employing ion trap confinement and sympathetic cooling techniques to mitigate the impact of the Doppler effect on 9Be2+ ions. Through molecular dynamics simulations, we investigated the influence of different ion systems on the temperature and efficiency of sympathetic cooling for 9Be2+ ions. Our findings offer valuable insights for future endeavors aimed at conducting high-precision spectroscopic measurements involving trapped and cooled 9Be2+ ions or other He-like ions.